The effect of advertising campaign on consumer buying behaviour: Petronas (M) Berhad - Mohamad Taufik, Ariffin (2023)
This study was conducted to investigate how advertising affected Petronas (M) Berhad consumer' purchasing Behaviour. The literature offered talks about the idea of advertising campaign and consumer purchasing behaviour. The researcher employed a descriptive and explanatory study methodology that quantitatively describes and explains the effect of advertising campaign on consumer purchasing behaviour. An information sample of 385 respondents was used. The independent variable was determined to be advertising campaign and the dependent variable was found to be consumer buying behaviour. Advertisements that are impressive, understandable, grabbling, and memorable were thought of as sub-variables of advertising. The collected information from those who responded was then examined. A two-tailed correlation analysis revealed a high and favourable link between consumers buying behaviour and advertisements that are impressive, understandable, attention grabbling, and memorable. The correlation research also shows a strong advertising campaign between consumers' buying behaviour and commercials that are compelling, memorable, and understandable. Additionally, multiple regressions were used. Based on the findings of this study, it is advised that effective advertising campaigns that use. The projections could be utilized to increase consumer and beat competitor. This study thus contributes a fresh perspective to the existing corpus of research that will aid scholars in their quest to comprehend how advertising influence consumer buying behaviour.